Experimental investigation of the effect of two steps on the performance and longitudinal stability of a mono-hull high-speed craft. Issue 1 (1st January 2020) - Sajedi, Sayyed Mahdi; Ghadimi, Parviz
Abstract: Transverse steps in modern high-speed craft can increase the longitudinal stability in addition to reducing frictional resistance. The porpoising instability can also be avoided by selecting the appropriate location and height of the transverse step. In the current paper, a non-step and a double-step model are investigated. The primary purpose of the present study is to examine the impact of second step on the stability and performance of the craft. Both models are generally identical. They are prismatic with a deadrise angle of 24 degrees, made of fiberglass, and are 2.64 meters long and 0.55 meters wide. The only difference between the two models is the bottom shape. One has two transverse steps, and the other has no step. These models are tested in a towing tank within a range of beam Froude numbers of 0.43 to 3.87. Measured parameters include rise-up of the bow and aft as well as center of gravity, trim, and resistance of the models. The obtained results indicate that through creating the second step, the longitudinal stability of the model increases, and the trim decreases. On the other hand, the double-step model has lower resistance in the pre-planing state.